Principles and Pedagogies in Jewish Education - Chazan, Barry (Springer Nature, 2022)
This book is aimed at improving contemporary educational practice by rooting it in clear analytical thinking. The book utilizes the analytic approach to philosophy of education to elucidate the meaning of the terms "education," "moral education," "indoctrination," "contemporary American Jewish education,''"informal Jewish education," "the Israel experience," and "Israel education." The final chapter of the book presents an educator's credo for twenty-first Jewish education and general education. This is an open access book.